2015
DOI: 10.1063/1.4928405
|View full text |Cite
|
Sign up to set email alerts
|

Large scale phononic metamaterials for seismic isolation

Abstract: A passively tunable acoustic metamaterial lens for selective ultrasonic excitationIn this work, we numerically examine structures that could be characterized as large scale phononic metamaterials. These novel structures could have band gaps in the frequency spectrum of seismic waves when their dimensions are chosen appropriately, thus raising the belief that they could be serious candidates for seismic isolation structures. Different and easy to fabricate structures were examined made from construction materia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 19 publications
0
19
0
2
Order By: Relevance
“…This particular property has opened an innovative direction to reduce earthquake-induced vibrations. [10][11][12] At the outset, two types of applications have been proposed based on this phenomenon: (1) foundations with embedded resonators [13][14][15][16] capable of attenuating seismic waves effects and (2) barriers that are able to redirect surface waves back into the ground. [17][18][19][20] More precisely, Cheng and Shi 14 studied a periodic foundation composed of a reinforced concrete matrix and steel masses that are connected to the matrix with rubber layers.…”
Section: Background and Motivationsmentioning
confidence: 99%
See 1 more Smart Citation
“…This particular property has opened an innovative direction to reduce earthquake-induced vibrations. [10][11][12] At the outset, two types of applications have been proposed based on this phenomenon: (1) foundations with embedded resonators [13][14][15][16] capable of attenuating seismic waves effects and (2) barriers that are able to redirect surface waves back into the ground. [17][18][19][20] More precisely, Cheng and Shi 14 studied a periodic foundation composed of a reinforced concrete matrix and steel masses that are connected to the matrix with rubber layers.…”
Section: Background and Motivationsmentioning
confidence: 99%
“…This is due to their capability to exhibit low‐frequency band gaps that can be endowed with unit cells much smaller than the wavelength of the desired frequency region. This particular property has opened an innovative direction to reduce earthquake‐induced vibrations . At the outset, two types of applications have been proposed based on this phenomenon: (1) foundations with embedded resonators capable of attenuating seismic waves effects and (2) barriers that are able to redirect surface waves back into the ground …”
Section: Introductionmentioning
confidence: 99%
“…The concept of metamaterials has been expanded to the elastoacoustic field in recent years. Such metamaterials are now widely applied in the fields of vibration and noise control [6][7][8][9][10], acoustic cloaking [11][12][13], seismic shields [14,15], acoustic wave lensing [16,17], wave trapping [18,19] and acoustic black holes [20,21] among other fields. Effective negative constants can be observed from elastic/acoustic metamaterials as well as electromagnetic metamaterials, including negative mass and dynamic stiffness [22][23][24], negative bulk modulus [25] and double negative characteristic [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…[27] In 2015, Aravantinos-Zafiris et al considered network topology and a variable cross-section structure. [28] Ungureanu et al found in 2015 that the propagation of seismic waves with a frequency between 1 and 40 Hz can be affected by auxetic-like Figure 2. The metawedge showing, in (a), the geometry and material parameters.…”
Section: Outer-shielded Smsmentioning
confidence: 99%